Owned By EbRaHiM-VaKeR t.me/ @Hajit00n - @LegionLeakers Thanks: AHORA - Special_One - H4 Expl0it3r: Owned By EbRaHiM-VaKeR t.me/ @Hajit00n - @LegionLeakers Thanks: AHORA - Special_One - H4 Expl0it3r - Aam Siti Maryam; Zaini Abdul Malik; Intan Manggala (Bandung Conference Series: Syariah Banking, 2025)
Abstract. BMT Beringharjo is a Sharia-based microfinance institution that plays an important role in supporting the development of Micro, Small, and Medium Enterprises (MSMEs). One of its main financing products is murabahah financing, a sale-and-purchase scheme with an agreed-upon profit margin in accordance with Islamic principles. This financing provides a fair alternative for MSME actors who need working capital while avoiding interest-based systems. This study aims to examine the process of providing murabahah financing at BMT Beringharjo Bandung and its influence on the business development of financing recipients. The research method used is quantitative by distributing questionnaires to 60 respondents who received murabahah financing. The data were analyzed using validity and reliability tests, as well as simple linear regression to measure the relationship between financing and business development, supported by qualitative descriptive data through observation and documentation. The results show that all indicators are valid and reliable, with a Cronbach's Alpha value of 0.878. A correlation coefficient of 0.753 and a determination coefficient of 0.568 indicate a positive and significant influence of murabahah financing on MSME development. This proves that murabahah financing is not only a financial solution but also contributes significantly to the growth and empowerment of microenterprises. Abstrak. BMT Beringharjo adalah lembaga keuangan mikro berbasis syariah yang berperan penting dalam mendukung pengembangan Usaha Mikro, Kecil, dan Menengah (UMKM). Salah satu produk utama yang ditawarkan adalah pembiayaan murabahah, yakni skema jual beli barang dengan margin keuntungan yang disepakati sesuai prinsip Islam. Pembiayaan ini menjadi alternatif yang adil bagi pelaku UMKM yang membutuhkan modal kerja tanpa sistem bunga. Penelitian ini bertujuan untuk mengetahui proses pemberian pembiayaan murabahah di BMT Beringharjo Bandung serta pengaruhnya terhadap perkembangan usaha penerima pembiayaan. Metode penelitian yang digunakan adalah kuantitatif melalui penyebaran kuesioner kepada 60 responden penerima pembiayaan. Analisis dilakukan dengan uji validitas, reliabilitas, serta regresi linear sederhana untuk mengukur hubungan antara pembiayaan dan perkembangan usaha, didukung data deskriptif kualitatif melalui observasi dan dokumentasi. Hasil penelitian menunjukkan seluruh indikator valid dan reliabel dengan nilai Cronbach’s Alpha 0,878. Koefisien korelasi sebesar 0,753 dan determinasi 0,568 menunjukkan pengaruh positif dan signifikan pembiayaan murabahah terhadap perkembangan UMKM. Hal ini membuktikan bahwa pembiayaan murabahah tidak hanya menjadi solusi keuangan, tetapi juga berkontribusi nyata dalam meningkatkan pertumbuhan dan pemberdayaan usaha mikro. Owned By EbRaHiM-VaKeR t.me/ @Hajit00n - @LegionLeakers Thanks: AHORA - Special_One - H4 Expl0it3r